Problematika Guru dalam Penyusunan Perangkat Pembelajaran Daring Dimasa Pandemi Covid-19 di SMP Binajaya, Bantul - Rizki Akmalia; Heri Kurnia (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The purpose of this research is to improve the teacher's understanding of learning devices, in this study describes the problem of teachers in compiling learning devices, obstacles. faced by teachers as well as the efforts made by teachers in overcoming these obstacles. The method used in this study is a method of kualiatative descriptive using three instruments, namely: Observation, interview and documentation used to data collection. The results of the study can be concluded: first, educators at Binajaya Junior High School can understand the purpose, purpose,and function of learning devices that include syllabus, RPP, teaching materials, media learning and assessment. Second, the problems faced by educators in Binajaya Junior High School in compiling learning devices are, (1) there are still teachers who do not compile RPP, (2) Teachers difficulty in determining the allocation of time, learning methods and indicators of competency achievement, (3) Teachers still find it difficult to make problem instruments for assessment, (4) And teachers still rarely make learning media only use existing ones. Third, the obstacles faced by teachers include: (1) time constraints, and busy teachers, (2) diverse student conditions, (3) teaching experiences that are less. The efforts made by The Master inthe nature of the preparation of learning devices are: (1) seeking information from the internet, (2) conducting discussions with fellow Teachers, (3) Teachers hcurrent always learn, (4) School hcurrent is able to always facilitate or equip the Teachers with trainings.